2006
DOI: 10.1063/1.2218464
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectroscopy on magnetization reversal dynamics of nanomagnets with electronic detection

Abstract: We demonstrate a detection method for microwave spectroscopy on magnetization reversal dynamics of nanomagnets. Measurement of the nanomagnet anisotropic magnetoresistance was used for probing how magnetization reversal is resonantly enhanced by microwave magnetic fields. We used Co strips of 2 µm × 130 nm × 40 nm, and microwave fields were applied via an on-chip coplanar wave guide. The method was applied for demonstrating single domain-wall resonance, and studying the role of resonant domain-wall dynamics in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…This feature was previously reported by Grollier et al [16], when the longitudinal magnetization reverses. In the longitudinal field geometry, the magnetization reversal does not take place by depinning of the pinned DW but rather by the nucleation of a reversed domain and subsequent DW propagation.…”
Section: Resultssupporting
confidence: 70%
“…This feature was previously reported by Grollier et al [16], when the longitudinal magnetization reverses. In the longitudinal field geometry, the magnetization reversal does not take place by depinning of the pinned DW but rather by the nucleation of a reversed domain and subsequent DW propagation.…”
Section: Resultssupporting
confidence: 70%
“…Above a threshold power of ÿ7 dBm, the depinning field starts to be strongly reduced for the resonant case, whereas the nonresonant current only weakly influences the depinning field due to heating. This pronounced nonlinear behavior points to a strongly nonharmonic potential as previously observed for field-induced resonance [31]. Such domain wall oscillators have recently been proposed theoretically [32], and the observed nonlinearity bodes well for a future possible device that would rely on phase locking a large number of wall oscillators.…”
Section: -3mentioning
confidence: 57%
“…Several other experiments confirmed the MAMR effect. Specifically, Grollier et al 5 demonstrated microwave-assisted reversal in cobalt strips by means of anisotropic magnetoresistance measurements; Nembach et al 6 and Pimentel et al 7 10,11 reported the observation of MAMR effects in Permalloy layers in magnetic tunnel junctions.…”
mentioning
confidence: 97%